Highly stable ladder-type conjugated polymer basedorganic electrochemical transistors for low power andsignal processing-free surface electromyogram triggered robotic hand control - Zhou, Zhongliang (2023)
Organic electrochemical transistors (OECTs) based complementary inverters have been considered as promising candidates in electrophysiological amplification, owing to their low power consumption, and high gain. To create complementary inverters, it is important to use highly stable p-type and n-type polymers with well-balanced current. In this work, we improved the electrochemical stability of p-type ladder-conjugated polymer based OECT through an annealing process where it maintained its doped-state drain current from 76 % to 105 % after 4,500 cycles in ambient environment. We next present an OECT-based complementary inverter made from p-type and n-type ladder-conjugated polymers (PBBTL and BBL) that possess ultra-low power consumption (~170 nW), high gain (67 V/V) and high noise margin (92%) with full rail-to-rail swing. Furthermore, we demonstrate its potential in amplifying the envelope of surface electromyography (EMG) for robotic hand control. The high variation in the output (0.35V) allows the amplified EMG signals to be directly captured by commercial analog-to-digital converter, which in turn controls the robot hand to grasp different objects with low delay and low noise. These results demonstrate the capability of OECT inverter based amplifier in future signal processing-free human machine interface, particularly useful for prosthetic control and gesture control applications.